2016
DOI: 10.1097/opx.0000000000000831
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gaze Position and Blur on Stepping Accuracy in Older Adults

Abstract: Increasing gaze position farther ahead from stepping locations and the presence of blur negatively impact the stepping accuracy of older adults. These findings indicate that blur, similar to that used in multifocal corrections, has the potential to increase the risk of trips and falls among older populations when negotiating challenging environments where precision stepping is required, particularly as gaze is directed farther ahead from stepping locations when walking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…1,2,4,5 Vision loss has been associated with increased risk for serious injuries, depression, delirium, chronic disease, and social health. [6][7][8][9][10][11][12][13] These conditions and associated sequelae can also affect quality of life generally, as well as reduce economic productivity. [1][2][3][14][15][16] Chemical burns to the eye are usually caused by either acidic or alkaline agents.…”
mentioning
confidence: 99%
“…1,2,4,5 Vision loss has been associated with increased risk for serious injuries, depression, delirium, chronic disease, and social health. [6][7][8][9][10][11][12][13] These conditions and associated sequelae can also affect quality of life generally, as well as reduce economic productivity. [1][2][3][14][15][16] Chemical burns to the eye are usually caused by either acidic or alkaline agents.…”
mentioning
confidence: 99%
“…Traumatic ocular events and their sequelae predispose patients to long-term physical, psychosocial, and economic effects, and sports-related events have been reported as a prominent contributor to the overall burden of ocular trauma. 9,10,12,43 Sports-related ocular trauma has been identified as a substantial risk factor for inpatient hospitalization, with some estimates suggesting that 22% to 40% of hospitalizations for ocular trauma were the result of injuries sustained during participation in sporting activities. 25,26,44 We have found that these injuries represent a substantial burden in EDs in the United States, accounting for approximately 30 000 ED visits annually-an estimate substantially higher than previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…The Centers for Disease Control and Prevention estimates that the annual rate of presentation to the emergency department (ED) for all-cause ocular injury is approximately 37.6 per 10 000 population . Eye injuries can have long-term sequelae that affect quality of life for years and can predispose the individual to further injury, depression, and systemic disease . Visual impairment also poses substantial economic challenges to patients, health systems, and payers, which may further affect the patient’s access to quality care and follow-up …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation